2013
DOI: 10.1371/journal.pone.0055328
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of CSF Cystatin C Levels and Their Correlations with CSF Αβ40 and Αβ42 Levels in Patients with Alzheimer's Disease, Dementia with Lewy Bodies and the Atrophic Form of General Paresis

Abstract: Immunohistochemical studies have revealed that cystatin C (CysC) co-localizes with amyloid-β (Αβ) in amyloid-laden vascular walls and in the senile plaque cores of amyloid. In vitro and in vivo animal studies suggest that CysC protects against neurodegeneration by inhibition of cysteine proteases, inhibition of Αβ aggregation, induction of autophagy and induction of cell division. CysC levels may be altered and may have a potential link with cerebrospinal fluid (CSF) Aβ levels in various types of dementia with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 42 publications
2
27
1
Order By: Relevance
“…A recent study demonstrated the presence of low CSF levels of cystatin C in patients with AD in comparison with healthy controls. 58 Although serum levels of cystatin C are presumably more related to renal dysfunction and CSF levels of cystatin C more to AD pathology, it is difficult to establish a one-to-one relationship due to intercorrelations.…”
Section: Continuedmentioning
confidence: 99%
“…A recent study demonstrated the presence of low CSF levels of cystatin C in patients with AD in comparison with healthy controls. 58 Although serum levels of cystatin C are presumably more related to renal dysfunction and CSF levels of cystatin C more to AD pathology, it is difficult to establish a one-to-one relationship due to intercorrelations.…”
Section: Continuedmentioning
confidence: 99%
“…Previous studies have found that CSF tau levels were increased in neurosyphilis versus controls [21] or that they were unchanged [22]. CSF levels of Aβ (1-42), which are believed to represent amyloid plaque pathology, were decreased in the atrophic form of general paresis [12,22]. Although neurosyphilis encompasses AD-like cognitive impairment [11] and AD-like decreases in CSF Aβ (1-42) [12], we found discrepancies in neuropsychiatric syndromes between neurosyphilis and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [11] showed a similar pattern of cognitive impairments in memory, language, and executive function between patients with neurosyphilis-dementia and patients with mild AD. Biologically, patients with AD and those with neurosyphilis-dementia appear to share decreased Aβ42 in the cerebral spinal fluid (CSF) [12]. Whether patients with neurosyphilis also share an AD-like pattern of neuropsychiatric symptoms is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic deletion of cystatin B and C has been shown to improve neurological deficits and restore autophagic dysfunction in the TgCRND8 and hAPP-J20 mouse models of AD [127,213]. However, conflicting reports indicate that cystatin C is neuroprotective in several neurodegenerative diseases, and these effects may be mediated by inducing autophagy [214][215][216][217]. Future studies should examine the effects of cystatins in AD [218], and whether neuroprotection is attenuated in the absence of autophagy.…”
Section: Trehalosementioning
confidence: 99%